2020
DOI: 10.1002/fsn3.1870
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aqueous ozone treatment on microbial growth, quality, and pesticide residue of fresh‐cut cabbage

Abstract: The influence of aqueous ozone (1.4 mg/L) treatment for 1, 5, and 10 min on the microbial growth and quality attributes of fresh‐cut cabbage during storage at 4°C for 12 days was evaluated. The pesticide residue removal effect of aqueous ozone treatment for 5 min was also determined. The results show that the growth rates of aerobic bacteria, coliforms, and yeasts were significantly inhibited (p < .05) by aqueous ozone treatment during storage; treatment for 10 min showed the greatest inactivation of bacteria,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 37 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…Liu et al, 2021 [63] Parsley leaves Aqueous ozone 12.0 mg L −1 compared with chlorine 100 mg L −1 (5 min)…”
Section: Literature Review Aims and Objectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al, 2021 [63] Parsley leaves Aqueous ozone 12.0 mg L −1 compared with chlorine 100 mg L −1 (5 min)…”
Section: Literature Review Aims and Objectivesmentioning
confidence: 99%
“…In order to control the negative effects of stress, modified atmosphere packaging has proven to be useful for storing minimally processed fruits and vegetables [107]. In fresh-cut cabbage and apple, the aqueous ozone treatment at 1.4 mg L −1 for 1, 5 and 10 min (cabbage) and 1 and 5 min (apple) stimulated the initial respiratory metabolism of cabbage and reduced ethylene production in fresh-cut apple and cabbage, thus enhancing the overall quality of the produce [63,94]. Following gaseous O 3 treatment with 6.34 mg m −3 for 4 h and storing for 12 days at 5 • C in commercial packaging, low respiration (0.61 µLC O 2 kg −1 h −1 ) and ethylene production rates (1.04 µL kg −1 h −1 ) were observed in minimally processed melon fruits [103].…”
Section: Physiological and Technological Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…It is highly prone to microbial contamination, development of objectional flavor, cut-surface browning, and textural failure. In this regard, Liu, Chen, et al (2021) studied the influence of AO treatment at 1.4 mg/L for 1, 5, and 10 min on the microbial profile and quality of freshly cut cabbage in the course of storage (4 • C). They observed that aerobic bacteria, coliforms, and yeasts got considerably inhibited by AO throughout storage, with 10 min treatment exhibiting the highest inactivation.…”
Section: Fruits and Vegetable Decontaminationmentioning
confidence: 99%
“…In addition, the ability of ozone to remove pesticide residues in foods has intensively been studied. For instance, 1.4 mg/L ozone-water-washing for 30 min was considered as an effective way to remove six pesticide residues and improve shelf life and safety of fresh-cut cabbage [ 11 ].…”
Section: Introductionmentioning
confidence: 99%